A 10-Year Surveillance of Eimeria spp. in Cattle and Buffaloes in a Mediterranean Area - Morgoglione, Maria Elena; Bosco, Antonio; Maurelli, Maria Paola; Alves, Leucio Camara; Saralli, Giorgio; Bruni, Gianpaolo; Cringoli, Giuseppe; Rinaldi, Laura (Frontiers in Veterinary Science, 2020)
Coccidiosis due to Eimeria spp. are widespread parasitic infections in cattle and water buffaloes and may impair health, welfare and production of these livestock species. The aims of this study were: i) to investigate the prevalence and seasonal dynamics of eimeriosis and ii) to characterize the Eimeria species in large ruminants in a Mediterranean area, in order to plan effective control strategies. Parasitological data were obtained from a 10-year surveillance programme (2010-2019) on 3,631 farms (2,089 buffalo and 1,542 cattle farms) sampled in central and southern Italy. Pooled faecal samples were analyzed using the FLOTAC technique with an analytic sensitivity of 2 oocysts per gram of faeces (OPG) utilizing a saturated sodium chloride flotation solution (specific gravity = 1.200). Eimeria species identification was performed by morphometric analysis after one-week incubation of oocysts in a 2.5% potassium dichromate solution. The results showed high prevalence of Eimeria (up to 100%) in both cattle and buffaloes in the 10 years of surveillance, even if a slight reduction was reported in the last three years. The overall prevalence of eimeriosis was 91.7% (95% Confidence Interval, 95%CI= 90.2-93.1) in cattle farms and 81.5% (95% CI= 79.8-83.1) in water buffalo farms. The mean OPG value was 66.8 (min=2; max= 8,065) in cattle and 55.9 (min=2; max= 15,415) in water buffaloes, but this difference was not statistically significant (p>0.05). In total 9 species of Eimeria were found in cattle the most prevalent being Eimeria bovis, E. ellipsoidalis, E. cylindrica and E. zuernii; whereas in water buffaloes 8 species of Eimeria were found, the most prevalent being E. ellipsoidalis, E. auburnensis, E. bovis and E. zuernii. Mixed infections were common in both ruminant species. The seasonal pattern showed a higher prevalence of eimeriosis in cattle in spring (86.9%) whereas in buffalo farms the prevalence was higher in winter (82.3%) and summer (82.4%). In conclusion, the 10-year surveillance programme indicates that eimeriosis is common in cattle and water buffaloes and therefore continuous effective control strategies are needed.